PWE-007 The Incidence Of Venous Thromboembolism In The Bowel Cancer Screening Programme. (9th June 2014) - Kwok, HYH; O'Sullivan, L; Down, C; Muller, AF
Abstract : Introduction: The Department of Health has published guidance stating that the development of venous thromboembolism (VTE) within 90 days of a Hospital event is a notifiable condition. 1 We have previously identified an increased risk of VTE 2 in patients attending for endoscopic procedures although this was confined to those with predisposing factors including malignancy. This study examined the incidence of VTE in patients with positive faecal occult blood tests attending for bowel cancer screening colonoscopy. Methods: Patients who participated in the bowel cancer screening programme in East Kent (BCSP) over a four year period from May 2009 to the end of April 2013 were included. Data was gathered from the 'Exeter' electronic database and cross referenced to the electronic radiology reporting system (PACS), to identify those patients with a history of VTE prior to, or within 90 days of colonoscopy (by Doppler Ultrasound, VQ scanning or Computerised Tomography of the Pulmonary Arteries – CTPA), a diagnosis of colon cancer made at colonoscopy; whether patients had been admitted for their procedures or had undergone surgery after the diagnosis. Results: Over the 4 year study period, 2296 patients attended for colonoscopy (F: 912; M: 1384, mean age 65.5 years). 203 patients (8.8%) were diagnosed with colorectal cancer (CRC). There were 10 cases of VTE post colonoscopy (CRC : 8; normal result : 2). In the 8 cases diagnosed with CRC and VTE, only 2 were diagnosed within 90 days post procedure (F: 2; at 21 days – bilateral PE's and 49 days – bilateral DVT's). They had not undergone surgery. Of the 2 patients with a normal colonoscopy result and VTE, none were diagnosed within 90 days post procedure. None of the VTE patients had a previous history of thrombosis or had been admitted for bowel preparation. Conclusion: The incidence of VTE in patients attending for colonoscopy in the BCSP is low, even in those patients diagnosed to have colorectal cancer. References: Commissioning for quality and innovation 2013/2014 Guidance. Dept of Health Feb. 2013 Venkatachalapathy SV et al . Endoscopy and the risk of venous thromboembolism: a case control study. Endoscopy International Open . In Press 2014 Disclosure of Interest: None Declared.